Structural style of inversion of rifts and passive margins: feedback between mountain building and surface processes - Huismans, R. S.; Beaumont, C. (TRABAJOS DE GEOLOGÍA, 2009)
Inversion of sedimentary basins and passive margins at various stages of their evolution is modelled with thermo-mechanical viscous-plastic finite element techniques. We focus on two aspects of the inversion and collision process: 1) the role of the strength of the lower crust on the style of inversion, and 2) feedback relations of surface processes with the tectonic deformation and their control on the style of lithosphere inversion. The model involves a 35 km thick crustal layer and a 125 km length lithosphere. All materials follow frictional-plastic strain softening, or thermally activated viscous flow laws. The model is thermally coupled and the thermal evolution is calculated. During a first phase, the model is extended to form a rift basin. The rift basin or passive margin geometry is then used as initial condition for a phase of lithosphere scale inversion and collision. Using a prior rift or passive margin formation phase allows examining the role of pre-existing heterogeneity on the style of inversion and continental collision. We examine the effect of very simple end member surface process models on the style of mountain building: 1) no erosion and no sedimentation, 2) no erosion and complete sedimentation, and 3) complete erosion and complete sedimentation. Very contrasting behavior is observed for these end-member variations in surface process model.